High-Fidelity simulation and its impact on non-technical skills development among healthcare professionals: a systematic review and meta-analysis - Vangone, Ida; Caruso, Rosario; Magon, Arianna; Giamblanco, Carmelo; Conte, Gianluca; Baroni, Irene; Russo, Sara; Belloni, Silvia; Arrigoni, Cristina (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: High-Fidelity Simulation (HFS) has emerged as a pivotal educational strategy in healthcare, particularly for bridging the gap between theoretical knowledge and practical application. This systematic review and meta-analysis aimed to investigate the efficacy of HFS in enhancing non-technical skills among healthcare professionals. Methods: The literature search was conducted in PubMed, Embase, Scopus, CINAHL, and Google Scholar covering the period from February 2012 to August 2023. The inclusion criteria focused on randomized controlled trials (RCTs) and quasi-experimental studies that assessed the impact of HFS on measurable non-technical skills. Quality assessment was performed using RoB2 for RCTs and ROBINS-I for quasi-experimental studies. A random-effects meta-analysis, sensitivity analysis, and subgroup analyses were conducted. Results: Six studies met the inclusion criteria. The meta-analysis revealed a significant positive impact of HFS on non-technical skills, with an overall effect size (SMD) of 1.433, 95% CI [0.695, 2.172]. However, substantial heterogeneity was observed (I² = 93.3%). Subgroup analyses indicated variations in effect sizes based on study design, specific non-technical skills domains, and geographic location. Notably, quasi-experimental studies showed a higher effect size compared to RCTs. Conclusions: HFS is an effective educational tool for improving non-technical skills among healthcare professionals, particularly in enhancing self-efficacy. However, the observed heterogeneity and variations in effect sizes underscore the need for more standardized and rigorous research to optimize the use of HFS in different educational and geographical contexts. Future studies should focus on addressing the methodological limitations and exploring the factors contributing to the variability in outcomes. (www.actabiomedica.it)